Successful Pregnancy Outcome in Antiphospholipid Antibody Syndrome with Several Comorbidities - Chowdhury, Liza; Razzak, Abbdur; Khan, Rokeya; Sultana, Hasina (Journal of Bangladesh College of Physicians and Surgeons, 2017)
The presence of antiphospholipid antibody (aPL) has been clearly shown to have an adverse effect on pregnancy outcome. These effects may be apparent in the first trimester, presenting as recurrent pregnancy loss, or may be associated with the later development of pre-eclampsia (PE), IUGR, placental abruption, pre-term delivery, and intrauterine death. Antiphospholipid antibodies accounts for 3-5% of patients with second trimester repetitive pregnancy losses. The frequency of foetal death & recurrent abortion in untreated patient is greater than 90%.We will discuss here a 26 years old pregnant lady who was diagnosed 06 months prior to this pregnancy during pre conceptional counseling as antiphospholipid syndrome (APLS), autoimmune hypothyroidism and hypertension. She was on aspirin, heparin & thyroxine and ovulation inducing drugs before conception. After conception she was on close monitoring by the Obstetrician and Medicine specialist and ultimately on 36th week pregnancy was terminated by LSCS & a female baby was delivered. However, although the live birth rate is increased sevenfold, it should be acknowledged that these births are associated with an increased rate of prematurity and possible neonatal complications. The increased incidence of pregnancy-related complications necessitates the need for careful antenatal surveillance, and for delivery to be conducted in a unit with facilities for operative delivery and neonatal intensive care. J Bangladesh Coll Phys Surg 2016; 34(3): 160-163